Micro-Enterprise innovation in Zimbabwe's Knowledge Economy: Navigating the contextual barriers to achieve business viability - Nyangulu, Rudo (Graduate School of Business (GSB), 2024)
Micro-enterprise firms in emerging markets facing scarcity tend to adopt unconventional strategies infused with innovation fuelling their enterprising efforts to achieve viability. The nature of the environment drives micro-enterprises to come together, forming business hubs in formal and informal structures relying on business theories to enable them to organise effectively. In such settings, traditional business theories cannot be applied in conventional ways; however, they can be utilised to innovate and create new processes. The theories identified in this study include national innovation systems (innovation systems) and business ecosystems driving knowledge generation and sharing. Underpinned by the theories of business model adaptation and collaborative bricolage. Bricolage typically regarded as a behavioural trait or skill that allows entrepreneurs and innovators to operate in challenging environments. Its practice is observed in economies like Zimbabwe, where micro-enterprise firms are constantly adapting to a constantly changing operating environment. This study examines the relationship between those micro-enterprises in the knowledge services sector as they selforganise in what has been identified as business ecosystems that rely on collaboration to cocreate thereby improving as well as developing new products for market. In discovering if there is a link between co-creation and sustainability in emerging markets, four overarching factors are considered to impact the significance of innovative co-creation approaches. These factors are, namely, structure, trust, reliability, and necessity. Structure relates to how they organise themselves (ecosystems); ‘trust' speaks to the depth of faith held among business hub members, and consideration of reputational risk. Reliability, quality, skills, and professionalism of each co-creator or collaborator; and necessity (the extent to which collaborative bricolage is used in co-creation in an economy characterised by scarcity). In this thesis, the research will explore, through qualitative inquiry, how these factors are leveraged by micro-enterprise firms. With the insight from this study, the research aims to determine an optimal operating model that allows the co-creating actors to minimise the impact of the volatile operating environment and reward participation proportionally to the cost they bear to foster conditions of reciprocity, enabling collaborative bricolage in an enabling ecosystem that leverages innovation systems to achieve business viability.